The impact of heat input on the strength, toughness, microhardness, microstructure and corrosion aspects of friction welded duplex stainless steel joints. (April 2015) - M, Mohammed Asif; Shrikrishna, Kulkarni Anup; Sathiya, P.; Goel, Sunkulp
Highlights: Good tensile strength over higher heat input by perfect adhesion friction surface. Increased microhardness with increase in heat input through refinement of grains. Decreased impact toughness with increase in heat input by austenite phase loss. Increased ferrite and nil intermetallic phases were found after friction welding. Higher heat input gives better corrosive resistance on weld than the base material. Abstract: The impact of heat input on mechanical aspects like joint strength, toughness, microhardness and metallurgical and corrosion characterization of UNS S31803 duplex stainless steel (DSS) in solid state continuous drive friction welding was studied. The experiments were carried out according to Design of Experiments (DOE) with L9 orthogonal array by varying the four different parameters namely friction pressure, friction time, upsetting pressure and upsetting time, keeping spindle speed as constant. Detailed analysis of fracture morphology, presence of elements and its distribution on joint zone were performed through scanning electron microscopy (SEM) attached with energy dispersive spectroscopy (EDS). No intermetallic phases were observed by X-ray diffraction (XRD) technique. Tensile strength results showed that higher the heat input the better was the preservation of joint strength. At room temperature, toughness decreased as heat input increased. At −100 °C and −196 °C, toughness of weld metal was comparatively higher than other fusion processes. Microhardness increased with an increase in heat input due to grain refinement. In addition, the corrosion behavior of the weld metal was also evaluated through potentio-dynamic polarization curve. Corrosion resistance of weld was better than that of base material and it is increased with an increase in the heat input.